2007
DOI: 10.2478/s11658-007-0023-0
|View full text |Cite
|
Sign up to set email alerts
|

The identification of QTLs associated with the in vitro response of rye (Secale cereale L.)

Abstract: This study was conducted in order to identify quantitative trait loci (QTLs) for the in vitro culture response of winter rye (Secale cereale L.) immature embryos and immature inflorescences. A genetic linkage map comprising 67 SSRs, 9 ISSRs, 13 SAMPLs, 7 RAPDs, 2 SCARs and one EST marker was created based on the analyses of 102 recombinant inbred lines from the cross between lines L318 (which has a good response in tissue cultures) and L9 (which is unable to regenerate plants from somatic tissues and anthers).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 33 publications
2
29
0
1
Order By: Relevance
“…The lack of response was found to be controlled by at least two interacting genes (RakoczyTrojanowska and Malepszy 1995). Bolibok et al (2007) reported that nine putative QTLs for rye tissue culture response have been mapped on chromosomes 1R, 4R, 5R, 6R and 7R. In our study four of QTLs connected with albino plants formation were found on chromosome 4R.…”
Section: Localization Of Genomic Regions Controlling Albino Plant Regsupporting
confidence: 56%
See 1 more Smart Citation
“…The lack of response was found to be controlled by at least two interacting genes (RakoczyTrojanowska and Malepszy 1995). Bolibok et al (2007) reported that nine putative QTLs for rye tissue culture response have been mapped on chromosomes 1R, 4R, 5R, 6R and 7R. In our study four of QTLs connected with albino plants formation were found on chromosome 4R.…”
Section: Localization Of Genomic Regions Controlling Albino Plant Regsupporting
confidence: 56%
“…Similar results were received by González et al (2005), who also detected QTLs for final efficiency of green plants regeneration on chromosome 4R on triticale genome. Moreover, callus induction and somatic embryogenesis ability in rye tissue cultures are also determined by loci located on this chromosome (Bolibok et al 2007).…”
Section: Localization Of Genomic Regions Controlling Albino Plant Regmentioning
confidence: 99%
“…In barley, QTLs controlling callus growth (CG), subsequent shoot differentiation ratio (SD) and green shoot ratio (GS) in immature embryo culture were identified using 99 recombinant inbred lines (RILs) (Mano et al, 2002). The identification of QTLs for the in vitro culture response of winter rye immature embryos and immature inflorescences was also carried out by Bolibok et al (2007). Numerous studies conducted on genetic control of plant tissue culture responses have shown that tissue culture performance is quantitatively controlled (Taguchi-Shiobara et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, a highly efficient regeneration system is a necessary prerequisite for successful utilization of such methods (Bolibok and Rakoczy-Trojanowska, 2006;Bolibok et al, 2007). So far, a number of regeneration systems and transformation systems have been established for many plant species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation